GAMBARAN RED BLOOD CELL DISTRIBUTION WIDTH (RDW) PADA IBU HAMIL TRIMESTER II DI PUSKESMAS POASIA - Sri Aprilianti Idris; Susanti Susanti; Fitrayana Sari (Jurnal Analis Kesehatan Kendari, 2021)
ABSTRACT Trimester II pregnant women is a pregnant woman with 15 weeks of gestation (week 13 to 27). Trimester II pregnant women often have iron deficiency anemia can affect the examination value of Red Blood Cell Distribution Width (RDW). Red Blood Cell Distribution Width (RDW) is the difference in size or extent of red blood cells. RDW changes are influenced by many factors such as anemia, renal dysfunction or liver dysfunction, hepatic dysfunction, thyroid disease, acute transfusion or chronic inflammation, neurohormonal activation, malnutrition (iron, vitamin B12 and folic acid), ethnicity, bone marrow suppression, and use of some medicines. This study aims to find out the description of Red Blood Cell Distribution Width (RDW) in Trimester II pregnant women at Puskesmas Poasia of Kendari City used analyzer hematology method. The type of this research is descriptive with sampling technique is accidental sampling technique, with the number of samples as much as 15 people. The results of a study of 15 patients of trimester II pregnant women at the Poasia Public Health Center in Kendari City, a normal RDW-SD score of 10 (66.7%) and a high of 5 (33.3%), a normal RDW-CV was 10 ( 66.7%) people and a high of 5 people (33.3%). Keywords : Trimester II pregnant women, Red Blood Cell Distribution Width ABSTRAK Ibu hamil trimester II adalah ibu hamil dengan usia kehamilan 15 minggu (minggu ke-13 hingga ke-27). Ibu hamil trimester II sering kali mengalami anemia defisiensi zat besi yang dapat mempengaruhi nilai pemeriksaan Red Blood Cell Distribution Width (RDW). Red Blood Cell Distribution Width (RDW) adalah perbedaan ukuran atau luas dari sel darah merah. Perubahan RDW dipengaruhi oleh banyak faktor seperti anemia, disfungsi ginjal atau disfungsi hati, penyakit tiroid, tranfusi, akut atau peradangan kronis, aktivasi neurohormonal, malnutrisi (zat besi, vitamin B12 dan asam folat), etnis, tulang depresi sumsum, dan penggunaan beberapa obat. Penelitian ini bertujuan untuk mengetahui Gambaran Red Blood Cell Distribution Width (RDW) pada Ibu Hamil Trimester II di Puskesmas Poasia Kota Kendari, menggunakan metode hematologi analyzer. Jenis penelitian ini adalah deskriptif dengan teknik pengambilan sampel accidental sampling, dengan jumlah sampel sebanyak 15 orang. Hasil penelitian terhadap 15 pasien ibu hamil trimester II di Puskesmas Poasia Kota Kendari diperoleh nilai RDW-SD normal sebanyak 10 (66,7%) orang dan yang tinggi sebanyak 5 orang (33,3%), RDW-CV normal sebanyak 10 (66,7%) orang dan yang tinggi sebanyak 5 orang (33,3%) . Kata Kunci : Ibu Hamil Trimester II, Red Blood Cell Distribution Width